OTTER CALF - A. KHAMAS, W.; A. ABBAS, Th.; H. ALI, A. (The Iraqi Journal of Veterinary Medicine, 1989)
A full term fetus showing congenital defects in the head and limbs. The calf had inferior brachygnathia combined with four limbs deformity. Failure of the horizontal plate of palatine bone to fuse with the palatine process of the maxillary bone. When the haed was sectioned, large fluid filled cavity revealed in the lateral ventricles. Other parts of the central nervous system apparentlly well developed. These findings were compared with similar defects in other animals described in the literature.